KETERKAITAN ANTARA POLA ASUH DAN INNER CHILD PADA PERKEMBANGAN ANAK USIA DINI: SEBUAH TINJAUAN KONSEPTUAL [THE RELATIONSHIP BETWEEN PARENTING PATTERNS AND INNER CHILD IN EARLY CHILDHOOD'S DEVELOPMENT: A CONCEPTUAL REVIEW] - Nuroh, Siti (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2022)
The purpose of this study was to describe the relationship between parenting and the inner child in early childhood development. This study uses a literature study approach with a descriptive type of research. The results of this study are three kinds of impacts of different parenting styles on early childhood development, namely: (1) If someone knows the inner child and is bad at responding, then it is also bad in producing responses when interacting; (2) If someone knows the inner child and is good at accepting it, it will give birth to good activities or interactions and be able to develop themselves to be even better; and (3) If a person is aware of the inner child and is able to process his wounds into positive or good things, then good things will also be born.